Save in Cloud, Access Anywhere: The Utilization of Cloud Computing in University Libraries for Library Service Delivery in Contemporary Age - Eneh, Anthonia C.; Oviri, Beatrice Uchenna; Ekhorutonmwen, Maria - Gorretti (NIU Journal of Educational Research, 2024)
Clouds computing as become a cornerstone of modern technology, allowing one to save data on remote servers, accessible from any device with an internet connection. This accessibility fosters inclusivity and expands the reach of library services beyond traditional boundaries. Thus, this study focused on the research “Save it on the cloud and access anywhere: the utilization of cloud computing in university libraries for Library Service Delivery in contemporary age” The multi-stage sampling procedure was used to select the sample for this study. First stage involved stratifying the Universities on the bases of geopolitical zones. Second stage, the Universities in the six states were further grouped according to Federal, State and Private. T18 Universities comprising Federal, State and Private. Final stage involved the use of purposive sampling of total population to draw respondents. An online Google form questionnaire was used for this study and was distributed to respondents through Nigerian Library Association state chapters’ online platforms. 157 questionnaire were sent back but 148 respondents accurately filled the form correctly, and as such were considered valid for analysis. Frequency simple percentage and Mean scores were used to analyze the received responses. Result of the analysis show that cloud computing technologies were utilized to a high extent. The challenges affecting utilization of cloud computing technology were Limited staff training on cloud technology usage, and Compatibility issues with existing systems impede integration. The possible strategies for enhancing utilization of cloud computing technology were allocating dedicated budget for cloud technology investments and implementing robust data security measures for cloud solutions. The study suggested, among other things that University library management should increase the training sessions or resources to help librarians know the importance of cloud computing technology and There’s need for collaboration between librarians, IT staff, University management and other stakeholder to ensure that infrastructure that will enhance the implementation of cloud computing technology in university libraries for library service delivery. Keywords: Cloud Computing, Storage, Accessibility, Service Delivery, Contemporary Age, Aniversity